2006
DOI: 10.1021/jp060730e
|View full text |Cite
|
Sign up to set email alerts
|

From Fractal to Nanorod Porphyrin J-Aggregates. Concentration-Induced Tuning of the Aggregate Size

Abstract: A structural change from fractal to nanorod J-aggregates of tetrakis(4-sulfonatophenyl)porphyrin has been obtained by acting on the intermolecular interaction potential. The size and shape of these self-assembled porphyrin clusters have been monitored under different experimental conditions, by means of polarized and depolarized dynamic light scattering and small and wide angle elastic light scattering. At sufficiently low porphyrin concentration and high ionic strength, the shielded repulsive potential seems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
93
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 67 publications
(87 reference statements)
6
93
1
Order By: Relevance
“…While at high concentration, BMIM þ ions may be apt to associate with each other [25,26] and then break partially the J-aggregates of TPPS due to larger molecular volume, as shown in Scheme 1. Therefore, a conclusion could be drawn that J-aggregation of TPPS is related with the structure and size of anions besides acidity [27], concentration of TPPS [28], ionic strength [23] and polarity of the solvents [29].…”
Section: Mechanism Of the Effect Of Ionic Species In Ils On The J-aggmentioning
confidence: 99%
“…While at high concentration, BMIM þ ions may be apt to associate with each other [25,26] and then break partially the J-aggregates of TPPS due to larger molecular volume, as shown in Scheme 1. Therefore, a conclusion could be drawn that J-aggregation of TPPS is related with the structure and size of anions besides acidity [27], concentration of TPPS [28], ionic strength [23] and polarity of the solvents [29].…”
Section: Mechanism Of the Effect Of Ionic Species In Ils On The J-aggmentioning
confidence: 99%
“…37 The hierarchical self-assembly processes show different thermodynamically and kinetically controlled paths related to porphyrin concentration and medium conditions such as pH and ionic strength. 3,8,9 The aggregation is driven by electrostatic (including hydrogen bonding) and hydrophobic interactions occurring between the adjacent porphyrins, and lead to arrays whose sizes span from nano- to microscale.…”
Section: Introductionmentioning
confidence: 99%
“…To characterize the films of (OD) 3 TPPS 3 at the air-water interface on neutral and acidic subphases p-A isotherms, ellipsometric measurement, Brewster angle microscopy (BAM) and reflection spectroscopy have been utilized. It has been observed that (OD) 3 TPPS 3 forms stable mono-molecular layers, exhibiting J-aggregation induced by the zwitterion formation on neutral and acidic pH subphases, which is remarkable considering that the TPPS 4 J-aggregation takes place exclusively in acidic solution [5][6][7][8][9][10][11][12][13][14]. Moreover, the J-aggregation is independent of the applied surface pressure, unlike to the behavior at basic medium [37].…”
Section: Introductionmentioning
confidence: 95%
“…Porphyrin J-aggregates have attracted the interest of several research groups, due to their peculiar structural and photophysical properties, rendering them potential candidates for applications in nonlinear optics, nanometer-sized photoconductors, light-harvesting systems, and catalysis [2][3][4]. In particular, the diacid form of the 5,10,15,20-tetrakis(4-sulfonatophenyl)porphyrin (TPPS 4 ) (see Scheme 1), under highly acidic conditions (usually at pH < 3), and/or in the presence of cationic species [5][6][7][8][9][10][11][12][13][14], leads to aggregates where the zwitterionic porphyrins are supposed to be arranged in a side-by-side stacking fashion, stabilized by a network connecting the negative sulfonate end-groups with the protonated pyrrole nitrogen atoms. These aggregates are characterized by a very narrow and red-shift J-band (at 490 nm), exhibiting a large resonant enhancement of the scattered light [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation